Application Of Neuroplasticity Principles In Primary School Learning : Analysis Of Instruments And Interviews With Teachers At Dharma Putra Primary School - Anwar Marasabesy; Asep Supena (Journal of International Multidisciplinary Research, 2025)
This study aims to examine in depth the application of neuroplasticity principles in learning at elementary schools, focusing on the teaching practices of five teachers at SDS Dharma Putra. Neuroplasticity, as a core concept in neuroscientific learning, describes the brain's ability to form, strengthen, or modify neural networks through experience, repetition, meaningful activities, and students' emotional involvement. Given the characteristics of elementary school students who are at a stage of cognitive development that is highly responsive to learning environment stimulation, a study of the application of neuroplasticity by teachers is important to ensure that the learning process is in line with the brain's working mechanisms.This study used a neuropsychological instrument measuring the dimensions of neuroplasticity to assess four main indicators, namely repetition & practice, dedicated time for review, use of interactive activities, and contextual learning that connects the material to students' real experiences. The data was reinforced through in-depth interviews and thematic analysis of the learning strategies applied by each teacher. The results showed variations in application between teachers. Some teachers showed strong implementation in interactive activities and contextual learning (score of 5), while structured repetition showed lower consistency (score of 3). The interview findings reinforced the instrument results by showing patterns of strategies such as the use of inspirational stories, educational games, quizzes with prizes, conveying the benefits of learning, and scaffolding through easy material as a starting point. This study concludes that the application of neuroplasticity principles is present in teachers' teaching practices, although the level of depth and routine still needs to be strengthened. The theoretical implication confirms that learning that integrates positive emotions, collaborative activities, planned repetition, and contextualization of material has the potential to have a significant impact on the formation of students' neural networks. Practically, this study provides recommendations for strengthening neuroscientific learning-based instructional design as an effort to optimize the learning process of elementary school students.